Intravenous iron-sucrose complex for treatment of Iron Deficiency Anaemia in Pregnancy - experience in an Obstetric Day Care Clinic in a Tertiary Hospital - Tan AE,; Siti SA, (Penerbit UKM, 2008)
A cross-sectional study was undertaken to evaluate if outpatient administration of in-travenous iron sucrose complex (Venofer) was a sensible option in treating iron defi-ciency anaemia during pregnancy and puerperium. A total of 120 patients with iron deficiency anaemia were recruited from the Obstetric Day Care Clinic at the Universiti Kebangsaan Malaysia Medical Centre (UKMMC) over 18 months from March 2003 to August 2004. The main outcome measures were haemoglobin increment, patients’compliance, adverse effects and saving from hospitalization fees. The pre-treatment haemoglobin (Hb) level was 8.5+0.85g/dl for the antenatal patient and 7.6+0.80 g/dl in the post-partum group. The mean post-treatment haemoglobin increment at day four-teenth was 3.52+0.75g/dl. One patient developed skin rash while another had low-grade pyrexia. Seven patients experienced mild metallic taste. There were no serious side effects or anaphylactic reactions. Ten patients (8.3%) did not complete their ther-apy - eight delivered before completion of treatment; another two defaulted following delivery. The average number of Venofer used was seven ampoules i.e. 700mg per person, most of them required three sessions to complete the course. Outpatient treatment allows each patient to save hospitalization fees of RM45 per day, which to-talled up to RM135 for a 3-days ward stay. An estimation of RM16,200 hospitalization fees for the 120 patients was avoided during the study period. In conclusion, outpatient treatment of anaemia in pregnancy and post-partum period using Venofer was safe and feasible, with high patient compliant and cost-savings from hospitalization fees